A COMPARATIVE STUDY OF INSULIN RESISTANCE IN PATIENTS OF POLYCYSTIC OVARY SYNDROME: Insulin Resistance in Polycystic Ovary Syndrome - Arif, Amena; Waheed, Palvasha; Anees, Robina; Rashid, Amir; Khan, Saleem Ahmed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the relationship between obesity and insulin resistance in polycystic ovary syndrome affected women.Study Design: Cross sectional comparative study.Place and Duration of Study: Multidisciplinary Lab-I of Department of Biochemistry, Army Medical College, Rawalpindi, in collaboration with Pakistan Naval Ship Hafeez Hospital, Islamabad from Feb 2018 to Jan 2019.Methodology: One hundred and five selected females (puberty till 25 years of age) were divided into three groups of 35 each. Blood samples were collected an overnight fast (from 8-11 AM). Serum level of insulin was measured and insulin resistance was calculated based on HOMA-IR.Results: HOMA-IR concentrations correlated directly with Basal Metabolic Index, fasting plasma glucose and serum insulin levels. Mean serum insulin level was also elevated in patients with polycystic ovary syndrome (normal weight & overweight) as compared to control subjects (7.4 ± 1.2 mIU/L & 9.1 ± 0.8 mIU/L vs 6.3 ± 1.1 mIU/L; p as 0.003). The insulin resistance was slightly higher in patients with polycystic ovary syndrome as compared to the control subjects (1.4 ± 0.3 & 1.7 ± 0.2 vs. 1.1 ± 0.3; p